English: diverse but unified: putting texts at the heart of the discipline - Clark, Billy; Giovanelli, Marcello; Macrae, Andrea (National Association for the Teaching of English, 2014)
Billy Clark, Marcello Giovanelli and Andrea Macrae argue that ‘language and literature’ points the way towards a coherent vision of English, both at school and at university, as a unified but diverse subject encompassing literature, language, drama, media and creative writing.